Association between strategic differentiation and firm leverage manipulation: Empirical evidence from China - Niu, Feng; Wang, Jiayi; Su, Wunhong (Frontiers in Psychology, 2023)
Based on the background of the implementation of China’s comprehensive deleveraging policy, this study investigates the association between strategic differentiation and leverage manipulation using A-share listed firms in Shanghai and Shenzhen markets from 2007 to 2020. The results show that the greater strategic differentiation, the higher the likelihood of firm leverage manipulation. Furthermore, the association between strategic differentiation on leverage manipulation is more significant for firms with higher short-term debt repayment pressure. However, auditors’ industry expertise weakens the positive relationship between strategic differentiation and firm leverage manipulation. Further results show that strategic differentiation increases the likelihood of leverage manipulation by increasing firm financing constraints. This study enriches the literature on leverage manipulation, provides empirical evidence on the economic consequences of strategic differentiation, is important for relevant government departments to implement deleveraging policies, and is a reference for investors’ decision-making.